Alveolar osteitis: the current state of knowledge - Dryla, Aleksandra; Szymoniuk, Michał; Rogatko, Kamil; Piecewicz-Szczęsna, Halina (Journal of Education, Health and Sport, 2022)
Introduction and purpose: Alveolar osteitis, also known as dry socket is a common complication after tooth extraction, especially third molar extraction. Taking into consideration only third molar extractions, the prevalence of dry socket reaches even 45%. The aim of this literature review was to describe current knowledge about etiology, risk factors, treatment, and prevention of dry socket. State of knowledge: The symptoms of alveolar osteitis most frequently are reported between the first and third post-extraction days and they include discomfort, lancing, and intense pain which radiates to the neck and ear. The etiopathogenesis of dry socket remains unclear. However, the currently accepted hypothesis describes a loss of formed after an extraction blood clot from the alveolar socket as the main cause of this pathology. Several factors may increase the risk of dry socket and include smoking, oral hygiene, female gender, oral contraceptive drugs, and anesthesia. In the treatment of alveolar osteitis, irrigation of the socket with chlorhexidine gluconate, iodopovidone, or physiological saline followed by filling the socket with intra-alveolar dressing constitute a current fundamental procedure. Plenty of substances are currently used as an intra-alveolar dressing. Part of them exhibits only pain-decreasing features, whereas some drugs can also stimulate the regeneration of treated tissue. In the prevention, the use of alveolar osteitis warm saline, antibiotics, chlorhexidine, ozone gas, or autologous platelet therapy may be useful maneuvers. Conclusion: This literature review summarizes the current state of knowledge about causes, risk factors, and therapeutic and preventive methods with regard to alveolar osteitis.